Friction Spot Joining of Aluminium Alloy AA 5052 To Pre-Holed Steel AISI 1006 By Extrusion Aluminium Into A Rivet Head Die - Isam Tareq Abdullah (Journal of Techniques)
This work aims to join an aluminium alloy together with a pre-holed carbon steel sheet by extrusion the aluminium through a steel hole with a rivet shape to avoid the joint pull out. AA 5052 and AISI 1006 sheets were assembled with a lap configuration such that the aluminium specimen was put over the steel. A rivet head die was put under the steel hole. The aluminium was extruded through the rivet head die passing through the steel hole using a friction spot technique by a rotating tool. Effect of the hole diameter, rotating speed and plunging depth of the tool on the rivet head dimensions and joints shear force and strength were analysed by the design of experiments method. Joint macrostructure was examined. The aluminium metal was successfully extruded with a rivet shape. The steel hole diameter exhibited the highest effect on the rivet head dimensions and the joints shear force. Increasing the plunging depth of the tool increased the joints shear strength. The joined samples failed by shearing the extruded aluminium at the steel hole surface without pull-out the formed rivet head. The joining mechanism occurred with a mechanical interlock and without formation inter-metallic compounds between the two materials. For the first time, the AA 5052 and pre-holed AISI 1006 sheets were joined by extrusion the aluminium through a solid rivet head. The maximum shear strength of the joint exceeded those of the AA 5052 by 55%.